FIBER FRACTION OF KEPOK BANANA PEEL FLOUR (Musa paradisiaca) FERMENTED BY GOAT RUMENT FLUIDS - T. N. I., KONI; SITU, M. (Majalah Ilmiah Peternakan, 2022)
This experiment was conducted to evaluate the fiber fraction of banana peel meal fermented by goat rumen flu- id. The experimental design used was completely randomized design with four treatments and six replicates. Four treatments were CR0: kepok banana peel meal + 0% goat rumen fluid, CR30: kepok banana peel meal + 30% goat rumen fluid, CR40: kepok banana peel meal + 40% goat rumen fluid, CR50: kepok banana peel meal + 50 % goat rumen fluid. This fermentation process during seven days. The variables observed were NDF, ADF, hemycellulosa, cellulose, and lignin. The data on the fiber fraction of banana peel meal was analyzed by analysis of variance and continued with Duncan s multiple range tests. NDF, ADF, cellulose, hemicellulose, and lignin of banana peel meal fermented by goat rumen fluid was lower than that without goat rumen fluid. The conclusion in this study was that the use of 30% goat rumen fluid contained ADF of 31.84%, NDF of 45.03%, cellulose of 13.27% and hemicellulose of 13.53% of kepok banana peel meal.